Importance of living arrangements and coparenting quality for young children's mental health after parental divorce: a cross-sectional parental survey - Anders Hjern; Emma Fransson; Raziye Salari; Malin Bergström; Robin Hognäs; Kersti Bergqvist (BMJ Publishing Group, 2021)
Background Parental separation has been associated with adverse child mental health outcomes in the literature. For school-aged children, joint physical custody (JPC), that is, spending equal time in both parents' homes after a divorce, has been associated with better health and well-being than single care arrangements. Preschool children's well-being in JPC is less studied. The aim of this study was to investigate the association of living arrangements and coparenting quality with mental health in preschool children after parental separation.Methods This cross-sectional population-based study includes 12 845 three-year-old children in Sweden. Mental health was measured by parental reports of the Strength and Difficulties Questionnaire and coparenting quality with a four-item scale. The living arrangements of the 642 children in non-intact families were categorised into JPC, living mostly with one parent and living only with one parent.Results Linear regression models, adjusted for sociodemographic confounders, showed an association between increased mental health problems and living mostly and only with one parent (B=1.18; 95% CI 0.37 to 2.00, and B=1.20; 95% CI 0.40 to 2.00, respectively), while children in intact families vs JPC did not differ significantly (B=−0.11; 95% CI −0.58 to 0.36). After adjusting the analyses for coparenting quality, differences in child mental health between the post divorce living arrangements were, however, minimal while children in intact families had more mental health problems compared with JPC (B=0.70; 95% CI 0.24 to 1.15). Factorial analysis of covariance revealed that low coparenting quality was more strongly related to mental health problems for children in intact families and JPC compared with children living mostly or only with one parent.Conclusions This study suggests that coparenting quality is a key determinant of mental health in preschool children and thus should be targeted in preventive interventions.